The Influence of School’s Culture and Principal’s Leadership Style on Teacher’s Performance - Widyawati, Ira; Lian, Bukman; Fitria, Happy (Yayasan Sembilan Pemuda Indonesia, 2024)
This research aims to influence the school culture and the leadership style of the school principal towards the performance of teachers in the state Junior high School in subdistrict Gelumbang. This research uses quantitative methods with a correlational approach. Analysis of the data used is a double linear regression analysis. Data analysis results concluded that: (1) A partial school culture had a significant effect on the teacher’s performance; (2) A partial variable of leadership style significantly affected the teacher’s performance; and (3) simultaneously the school culture and leadership style of the headmaster has a significant impact on the performance of teachers in the state Junior high School, Gelumbang sub-district